Identifikasi Jenis Cedera pada Atlet Para Taekwondo dan Strategi Pencegahannya - Utomo, Andy Widhiya Bayu; Albar, Faiz; Septianingrum, Kartika; Dhani , Danang Prama (Universitas Hamzanwadi, 2025)
This study aims to identify the types of injuries experienced by para taekwondo athletes at the Central Java Regional Training Center (Puslatda), as well as to analyze the factors causing the injuries and their impact on athlete performance. A total of 17 athletes, comprising 11 male athletes and 6 female athletes, categorized as K41, K42, and K44, participated in this study. The method used was a quantitative descriptive study with a census approach. The results showed that the most common injuries were hamstring and ankle injuries, each experienced by 100% of the athletes. Additionally, pain injuries and swelling injuries were also frequently reported. The primary causes of injuries were collisions during kicking, overtraining, and technical errors in kicking. Injury management was carried out using the R.I.C.E method and medical support from KONI and hospitals. Most athletes continued their regular training or light training after the injury. This study concluded that technical errors and overtraining are the main causes of injuries, and proper training management and correct techniques are crucial to prevent further injuries.